ADMISSIBILITY OF EVIDENCE IN CRIMINAL PROCEEDINGS AND CRIMINAL LIABILITY FOR ITS VIOLATION - Kudryavtsev, Vladislav; Khimicheva, Olga; Prokofeva, Svetlana; Latypov, Vadim; Latypova, Nataliia (Revista Inclusiones, 2020)
The article deals with the problems of criteria-based admissibility of evidence in criminal proceedings, which are considered through the prism of bringing a person to criminal responsibility for falsifying evidence. The paper draws several conclusions. Firstly, not every violation of the criteria for admissibility of evidence leads to criminal liability, but that committed with direct intent and associated with the falsification of evidence by subjects of criminal responsibility. Secondly, there is a difference in the subject composition between subjects of admissibility of evidence and subjects of criminal liability for falsification of evidence. Thirdly, when falsifying evidence, the subject forms the state of the proper source of evidence, the proper method of collecting evidence, and the proper procedure for conducting a procedural action, which should not be in reality. The article has a scientific value, representing a comprehensive analysis of interrelated and mutually dependent criminal procedure problems of admissibility of evidence and criminal liability for its violation.